Necrotizing Fasciitis and Pyomyositis Caused by Streptococcus pyogenes: A Case Report - Barilli, Sofia Louise Santin; Zucatti, Paula Buchs; Maciel, Fabiana Henriques; Santos, Adriana Alves dos; Peruzzo, Anaelí Brandelli; Almeida, Rafaela dos Santos Charão de (Estima – Brazilian Journal of Enterostomal Therapy, 2025)
Objective: To report the case of a patient with streptococcemia caused by Streptococcus pyogenes progressing to necrotizing fasciitis and pyomyositis. Method: This case report was conducted in the intensive care unit (ICU) of a large public hospital in August 2023. The study was approved by a Research Ethics Committee. Results: A 15-year-old female patient was admitted to the emergency department with severe pain, edema, and a bullous lesion on the left upper limb (LUL). She rapidly progressed to septic shock due to necrotizing fasciitis with extensive soft tissue damage, and invasive streptococcemia caused by Streptococcus pyogenes was confirmed. The patient was transferred to the ICU, peripheral blood cultures were collected, and broad-spectrum antibiotic therapy was initiated. She was managed by a multidisciplinary team, including general surgery, plastic surgery, intensive care nurses, and wound care specialists. The treatment included fasciotomy and repeated mechanical debridements. Specific wound care strategies were implemented, involving the use of silver hydrofiber dressings, silicone dressings, and hydroactive gel. Subsequently, the patient was electively readmitted for a split-thickness skin graft on the LUL and continued outpatient follow-up with wound care specialists, showing excellent clinical progress. Conclusion: Invasive streptococcemia is a challenging condition due to its rapid progression and high mortality, requiring urgent and comprehensive management. Timely diagnosis, appropriate antibiotic therapy, immediate surgical intervention, and intensive multidisciplinary support, including advanced wound care, were crucial to achieving a favorable outcome.